Utilisation des résines échangeuses d’ions pour le nettoyage d’objets métalliques archéologiques ou historiques - Marietta Carlino; Elodie Guilminot (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Ion exchange resin was first synthesized in 1930 and is still widely used, mainly for water purification. The compound has already been used in certain restoration operations; however, at present there is no literature dealing with the exchange processes that occur when resins are used for this purpose. What criteria should be taken into consideration when selecting an ion exchange resin, and what exchange reactions take place? In this study, we focused on the elimination of Cu carbonates by testing 2 anionic resins and 2 cationic resins with different polymer matrices and exchanger groups.